MEMBUMIKAN EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) DI INDONESIA DALAM MENGHADAPI ISU – ISU GLOBAL - Putu Wulandari Tristananda (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
This article deals with a literature review of internalizing Education of SustainableDevelopment (ESD) in Indonesia. The important point about ESD relates to the issue of howeducational institutions, includes Indonesia should respond to the challenges and opportunitiesposed by the idea of sustainability. ESD aims at developing competencies that empower individualsto reflect on their own actions, taking into account their current and future social, economic andenvironmental impacts, from a local and a global perspective. ESD has to be understood as anintegral part of quality education, inherent in the concept of lifelong learning: All educationalinstitutions – from preschool to tertiary education and in non-formal and informal education –can and should consider it their responsibility to deal intensively with matters of sustainabledevelopment and to foster the development of sustainability competencies. ESD is holistic andtransformational education that addresses learning content and outcomes, pedagogy and thelearning environment. Thus, ESD does not only integrate contents such as climate change, povertyand sustainable consumption into the curriculum; it also creates interactive, learner-centredteaching and learning settings.Keywords: Education of Sustainable Development, Environment Education, Sustainability